2011
DOI: 10.1080/00380768.2011.629176
|View full text |Cite
|
Sign up to set email alerts
|

Tea plant (Camellia sinensisL.) roots secrete oxalic acid and caffeine into medium containing aluminum

Abstract: We examined the response of the tea plant (Camellia sinensis L.) to aluminum (Al) exposure under sterile conditions, focusing specifically on the secretion of low molecular mass organic compounds from roots. After germination in agar medium, tea seedlings together with medium were placed on agar containing 0.4 mM Al with 0.2% hematoxyline (hematoxylin-Al medium). The purple color of the hematoxylin-Al medium was observed to fade gradually, until none of the color remained 6 days later. The tea seedlings were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…For example, an in planta complementation assay indicated that tea contains a functional CsSTOP1, while physiological studies indicated that it has Al-tolerance mechanisms different from those in other species. Tea plants and cultured cells released oxalic acid in response to Al (Morita et al, 2008(Morita et al, , 2011. The release of oxalic acid is one of the major Al-tolerance mechanisms previously identified in other plants, including buckwheat (Fagopyrum esculentum; Zheng et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an in planta complementation assay indicated that tea contains a functional CsSTOP1, while physiological studies indicated that it has Al-tolerance mechanisms different from those in other species. Tea plants and cultured cells released oxalic acid in response to Al (Morita et al, 2008(Morita et al, , 2011. The release of oxalic acid is one of the major Al-tolerance mechanisms previously identified in other plants, including buckwheat (Fagopyrum esculentum; Zheng et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Proposed compounds include polypeptides, phenolic compounds, cyclic hydroxamates, and rhizodepositions in the form of mucilage (Jones and Ryan, 2003; Poschenrieder et al, 2008). In the tea plant, Camellia sinensis , Morita et al (2011) observed beside of oxalate an increase of the release of caffeine, a phenolic compound, in response to Al 3 + exposure. Phenolic compounds were also exuded in Al 3 + -treated Eucalyptus camaldulensis and two Melaleuca species (Nguyen et al, 2003).…”
Section: Al3+ Exclusionmentioning
confidence: 97%
“…One strategy for plants to utilize oxalate against Al toxicity relies on the secretion of oxalate from Al-stressed roots, thereby chelating Al to form nontoxic complex. For example, secretion of oxalate from plant roots in response to Al stress has been reported in taro (Colocasia esculenta; Ma and Miyasaka, 1998), common buckwheat (Fagopyrum esculentum; Zheng et al, 1998), tartary buckwheat (Fagopyrum tataricum; Yang et al, 2011b), tomato (Yang et al, 2011a), spinach (Spinacia oleracea; Yang et al, 2005), Polygonum species (You et al, 2005), tea (Camellia sinensis; Morita et al, 2011), and grain amaranth (Amaranthus hypochondriacus; Fan et al, 2016). Our previous study found that all oxalate accumulators including eight cultivars within four species were able to secrete oxalate in response to Al stress (Yang et al, 2008).…”
mentioning
confidence: 99%